Formulation and Evaluation of Biopolymer Based Buccal Film of Diclofenac Sodium (Journal of Basic and Applied Research in Biomedicine, 2022)
Buccal drug delivery gives easier and safe method of drug administration because in case of toxicity it can be terminated by simply removing the dosage form from buccal cavity. The buccal film of diclofenac sodium was prepared for systemic delivery by solvent casting method using sodium alginate and Ocimum Basilicum mucilage. Then film was evaluated for parameter like physical appearance, surface texture, mass uniformity, thickness, folding endurance, drug content and in vitro drug release. The results of evaluation test reveals that prepared film was smooth, have adequate folding endurance. The film shows percentage cumulative drug release of 67.57% at the end of 4 hrs.